Chronic Recreational Physical Inactivity and Epithelial Ovarian Cancer Risk: Evidence From the Ovarian Cancer Association Consortium. Issue 9 (September 2016) - Cannioto, Rikki; LaMonte, Michael J.; Risch, Harvey A.; Hong, Chi-Chen; Sucheston-Campbell, Lara E.; Eng, Kevin H.; Szender, J. Brian; Chang-Claude, Jenny; Schmalfeldt, Barbara; Klapdor, Ruediger; Gower, Emily; Minlikeeva, Albina N.; et al.
Abstract : (Abstracted from Cancer Epidemiol Biomarkers Prev 2016;25(7):1114–1124) It is estimated that 5% of women in the United States and 10% to 50% of women worldwide are physically inactive. Previous studies have demonstrated that recreational physical activity is associated with decreased risks of developing breast, colon, and endometrial cancers.